Higher Urine Exosomal miR-193a Is Associated With a Higher Probability of Primary Focal Segmental Glomerulosclerosis and an Increased Risk of Poor Prognosis Among Children With Nephrotic Syndrome - Wang, Lixia; Wang, Jie; Wang, Zhimin; Zhou, Jianhua; Zhang, Yu (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: In children, focal segmental glomerulosclerosis (FSGS) is one of the most common primary glomerular diseases leading to end-stage renal disease. Exosomes facilitate communication between cells by transporting proteins and microRNAs. We aimed to investigate the utility of urine exosomal miR-193a for diagnosis and prognosis estimation among patients with primary FSGS, and preliminarily explore the regulation mechanism of exosome secretion from podocytes. Methods: Specimens of urine were obtained from patients with primary FSGS, minimal change nephropathy (MCN) and IgA nephropathy (IgAN), followed by exosome isolation. We quantified urine exosomal miR-193a based on quantitative reverse transcription-polymerase chain reaction, and evaluated its applicability using area-under-receiver-operating-characteristics curves (AUROCs). The semiquantitative glomerulosclerosis index (GSI) was used to evaluate the degree of glomerulosclerosis according to the method of Raij et al. We further used FAM-labeled miR-193a-5p to examine exosome shuttling using confocal microscopy for visualization, and explored the regulation mechanism of exosomes release from podocytes using Fluo-3AM dye. Results: Urine exosomal miR-193a levels were significantly higher in patients with primary FSGS than those with MCN and IgAN. The AUROCs for discriminating between primary FSGS and MCN or IgAN were 0.85 and 0.821, respectively. Urine exosomal miR-193a levels positively correlated with GSI in patients with primary FSGS. We further found that kidney tissues from these patients had increased CD63 expression involving podocytes in non-sclerotic tufts. Exosomes from cultured podocytes could transport miR-193a-5p to recipient cells, potentially through a calcium-dependent release mechanism. Conclusion: Urine exosomal miR-193a might be harnessed as a non-invasive marker for diagnosis and outcome assessment among patients with primary FSGS. Exosomes were potential vehicles for miRNAs shuttling between podocytes, and released from podocytes in a calcium-dependent manner.